面向华裔学生的“听说+读写”中文教学模式探析——以印尼共同希望语言学院2023级大专班为例 - Ming Yue (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
Teaching model is one of the key factors to improve teaching quality. In view of the tendency of the current international Chinese teaching model to focus on structure and knowledge, but not on pragmatics and ability, the Chinese Language and Literature College of Jinan University in China has innovated a set of